The Effect of Social Media Content Marketing on Generation Y Customer Loyalty in Thailand’s Cosmetics Business - Silaruengnon, Suwaphit; Pansuppawatt, Areerat; Luangsakdapich, Rujira (MBA-KKU Journal, 2026)
The purpose of this research is to examine the effect of social media content marketing on customer loyalty among Generation Y in Thailand’s cosmetics business. Data were collected from 400 Generation Y social media users in Thailand using a questionnaire. The statistical methods used for data analysis included multiple correlation analysis and multiple regression analysis. The results of the study showed that content marketing on social media had a positive relationship with and a positive effect on overall customer loyalty. Therefore, cosmetic businesses in Thailand should prioritize social media content marketing to develop content that attracts customer attention, provides easy-to-understand, creative, and engaging information, reaches target customers effectively, and aligns with customers’ needs. Additionally, effective content marketing should help build customer trust and confidence in the brand. The effective implementation of social media content marketing will lead to customer loyalty, as reflected in repeat purchases driven by customers’ product satisfaction and positive experiences, as well as their willingness to recommend products or services to others.